2009
DOI: 10.1002/lsm.20840
|View full text |Cite
|
Sign up to set email alerts
|

Blood flow dynamics after laser therapy of port wine stain birthmarks

Abstract: Background and Objective During laser therapy of port wine stain (PWS) birthmarks, regions of perfusion may persist. We hypothesize that such regions are not readily observable even when laser surgery is performed by highly experienced clinicians. The objective of this study was to use objective feedback to assess the acute vascular response to laser therapy. Study Design/Materials and Methods A clinic-friendly laser speckle imaging (LSI) instrument was developed to provide the clinician with real-time image… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
10

Relationship

7
3

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 24 publications
0
30
0
Order By: Relevance
“…With LSI measurements collected before and after laser therapy, we identified that regions of persistent perfusion oftentimes existed after treatment [121, 122]. We postulated that immediate re-treatment of these regions would lead to an improved treatment response, which then would result in a decrease in the number of required treatment sessions to achieve complete PWS blanching.…”
Section: Real-time Clinical Laser Speckle Imaging During Pulsed-dmentioning
confidence: 99%
“…With LSI measurements collected before and after laser therapy, we identified that regions of persistent perfusion oftentimes existed after treatment [121, 122]. We postulated that immediate re-treatment of these regions would lead to an improved treatment response, which then would result in a decrease in the number of required treatment sessions to achieve complete PWS blanching.…”
Section: Real-time Clinical Laser Speckle Imaging During Pulsed-dmentioning
confidence: 99%
“…To date, laser Doppler perfusion imaging [6], optical Doppler tomography [7], cross-polarized diffuse reflectance imaging [8], fluorescence spectroscopy [9], laser speckle imaging [10][11][12] and spatial frequency domain imaging [13] have been used in attempting to predict or determine the therapeutic efficacy of photodynamic or laser treatments of PWS. In comparison to the above mentioned techniques, diffuse reflectance spectroscopy (DRS) with a fiber-optic probe can non-invasively quantify the optical properties of biological tissues and has demonstrated its great potential as a cost-effective, fast and sensitive tool for tissue diagnosis and monitoring in medical clinics [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Researchers have used LSI in a variety of pilot clinical tests to monitor local blood-flow changes. [5][6][7] However, LSI is not used for routine hemodynamic monitoring in the clinic, mainly due to a lack of standardized instrumentation. We and other groups previously demonstrated that a mounted LSI device with sensitivity to blood-flow dynamics can be created with the use of inexpensive, consumer-grade electronics.…”
Section: Introductionmentioning
confidence: 99%